Transmission Dynamics of Urogenital Schistosomiasis in the Rural Community of Ebonyi State, South Eastern Nigeria - F. N. Afiukwa; D. E. Nwele; O. E. Uguru; G. A. Ibiam; C. S. Onwe; A. U. Ikpo; N. B. Agumah; O. F. Odoemena (Journal of Parasitology Research)
This study accessed the dynamics of urogenital schistosomiasis transmission in Nkalagu Community. A total of 500 mid-day urine samples were collected and transported to Microbiology Laboratory, Ebonyi State University, for analysis. 10ml each of the urine samples was centrifuged at 2500 rpm for 5 minutes. Transmission potential of snail intermediate host of Schistosomes collected from different sampling station at the transmission sites within the study community was equally accessed. The snail species collected were placed individually into a clean beaker with little quantity of water and then subjected to shedding light for 2 hours. Data obtained were entered in excel spread sheet and analyzed using chi square test. The result obtained shows that 205 (41%) out of 500 individuals examined were excreting S. haematobium ova in their urine. The highest prevalence of infection (23%) was found among 11-20-year age groups. Males were more infected (25.4%) than their female counterparts (15.6%), although this was not statistically significant (p > 0.05). A total of 283 snails belonging to two Bulinus species (B. globosus and B. truncatus) were collected from the four sites sampled. Bulinus globosus recorded the highest species abundance (177) with the highest occurrence in site A. 52 (18.4%) out of 283 snails collected were infected with cercariae, and the highest cercariae infection (12.0%) was recorded among B. globosus. With prevalence of 41% among the human population and the prevalence of 18.4% patent infection among the snail intermediate hosts, urogenital schistosomiasis is still a public health problem in the study area and falls within the WHO classification of endemic area. Public health campaign is recommended in order to educate the people on the mode of transmission and control of the disease.